Design of Green Energy Stove: Characteristics of Combustion and Performance - Kurniawan, Stephanus Danny; Sasongko, Beni Tri (SENATIK STT Adisutjipto, 2018)
So far, the rural population of fuel users make firewood stoves from ground or cement. Often waiting is made less efficient and produces a lot of smoke pollution, especially if the level of dryness of the wood is low. From this background, then came the idea for the manufacture of stoves that save fuel wood and minimal smoke pollution. Furthermore, to be able to achieve this goal, in this study a biomass furnace will be developed that has a combustion air regulation system and a firewood drying system before use. Research implementation is divided into furnace design (design and fabrication) and testing (combustion characteristics and performance). Research begins with the design of the dimensions and shape of the furnace to be made. Furthermore, fabrication of stoves from Stainless Steel plate materials will be carried out at the Mechanical Technology Laboratory, IST AKPRIND. The stove produced by the construction will be tested with fuel wood in terms of combustion characteristics and performance. The results show that biomass stoves can be used and produced for household and small-scale industries.